Kompleksitas Regulasi Administrasi Keimigrasian dan Tantangannya dalam Globalisasi - Daffa Raihan Arya Mas’adi (Lembaga Pengembangan Kinerja Dosen, 2026)
The complexity of immigration administration regulations is a strategic challenge in maintaining state sovereignty while meeting the demands of globalization. Layered, overlapping, and asynchronous regulations between agencies often cause legal uncertainty, convoluted bureaucracy, and reduce the effectiveness of public services. This condition has an impact on declining public satisfaction, weakening institutional accountability, and opening up loopholes for maladministration and potential abuse of authority. In the context of globalization, cross-border human mobility is increasing, both due to economic, educational, tourism, and international migration factors, thus demanding simpler, adaptive, and responsive regulations. In addition, the complexity of regulations also has direct implications for national security aspects, especially in dealing with transnational threats such as terrorism, human trafficking, and abuse of residence permits. This study uses a qualitative method with a descriptive-analytical approach through literature studies and regulatory studies. The analysis shows that regulatory harmonization, the use of digital technology, and community involvement are key factors to reduce complexity while increasing the effectiveness of immigration governance. Regulatory reform is not just an administrative step, but a national policy strategy to strengthen public services, improve the image of global diplomacy, and maintain national security stability in the midst of increasingly complex global dynamics.